2012
DOI: 10.1038/ijo.2012.14
|View full text |Cite
|
Sign up to set email alerts
|

The A-allele of the common FTO gene variant rs9939609 complicates weight maintenance in severe obese patients

Abstract: In this program, the AA-genotype of rs9939609 was associated with a higher initial body weight and did influence success of weight stabilization. Thus, emphasizing the maintenance phase during a weight reduction program might result in better success for AA-genotype carriers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 26 publications
3
23
1
Order By: Relevance
“…A detailed screening flow is shown in Figure 1. Of the 14 selected articles, 10 reported the results of an additive genetic model (TA compared with TT, AA compared with TT) (6,7,11,12,(16)(17)(18)(19)(20)(21), whereas the other 4 articles reported the results of a dominant genetic model (TA/AA compared with TT) (13,15,25,26), which was mainly the result of limited sample size in these 4 studies. Given the known additive genetic effect of FTO variant on BMI and obesity risk, our primary analyses focused on the 10 studies that reported additive genetic model results.…”
Section: Results Of Literature Searchmentioning
confidence: 89%
See 2 more Smart Citations
“…A detailed screening flow is shown in Figure 1. Of the 14 selected articles, 10 reported the results of an additive genetic model (TA compared with TT, AA compared with TT) (6,7,11,12,(16)(17)(18)(19)(20)(21), whereas the other 4 articles reported the results of a dominant genetic model (TA/AA compared with TT) (13,15,25,26), which was mainly the result of limited sample size in these 4 studies. Given the known additive genetic effect of FTO variant on BMI and obesity risk, our primary analyses focused on the 10 studies that reported additive genetic model results.…”
Section: Results Of Literature Searchmentioning
confidence: 89%
“…One study explicitly mentioned that the model was unadjusted (25). For the other 4 studies (13,15,16,18), no information was provided regarding the statistical adjustment.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, it has been shown that physical inactivity was associated with a BMI increase (1.95 ± 0.3 kg/m 2 ) in homozygous A-allele carriers compared with homozygous T-allele carriers (Andreasen et al 2008). The FTO genotype has also been shown to interact with weight loss (Delahanty et al 2012), and the A-allele seems to complicate weight maintenance in severe obese patients (Woehning et al 2013). Studies also show that the A-allele is associated with increased energy intake (Speakman et al 2008), but this could not be confirmed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Individual lifestyle factors, such as eating habits or physical activity, are major contributors to the development of obesity (Ogden et al 2007). However, various genetic and neurobiological factors are also acknowledged to impact on the pathogenesis of obesity Need et al 2006;Bray 2006;Rankinen et al 2006;Winkler et al 2012;Woehning et al 2012).…”
Section: Introductionmentioning
confidence: 99%